Forensic Valuation of Intellectual Property - A. Ya. Asnis; M. A. Ivanova; Sh. N. Khaziev (Теория и практика судебной экспертизы, 2019)
Valuation of objects of intellectual property can be important when considering civil disputes, criminal cases of copyright and related rights infringements, criminal bankruptcies, cases of administrative offenses (violations of copyright and related rights, inventor’s and patent rights). At present, there is no generally accepted and accessible methodology of forensic valuation of intellectual property items.The main aspects of the forensic valuation of intellectual property are reviewed. It is shown that when assessing the value of intellectual property special knowledge should be applied in the field of forensic merchandising expertise, forensic economics, as well as other kinds and types of forensic expertise according to the characteristics of the intellectual property in question: forensic trace evidence analysis, computer forensics, forensic linguistics, forensic materials analysis, etc. It is necessary to develop and implement a new type of forensic examination in the forensic institutions of the Ministry of Justice of the Russian Federation - forensic examination of intellectual property which will also include the value assessment of such objects.